(untitled) (Journal “Crop Production, Selection And Seed Production, Fruit And Vegetable Growing”, 2026)
It is given the estimation of the seedling quality of tomato hybrids depending on the composition of the substrate in terms of film greenhouses. The quality of seedlings of tomato hybrids is assessed depending on the composition of the substrate when grown in film greenhouses. In crop production, there is an increasing tendency to use various substrates when growing vegetable crops in greenhouses, since, given the limited agricultural area and changing climatic conditions, the sustainable development of greenhouse vegetable growing is impossible without the introduction of advanced cultivation technologies into production. It has been shown that the physicochemical properties of the substrate provide sufficient fixation of plants, serve as a reservoir for nutrients and water, allow oxygen to diffuse to the roots and almost do not limit gas exchange between the roots and the atmosphere. The use of substrates allows you to increase the efficiency of cultivation and the quality of tomato seedlings. It has been shown that the development and quality of seedlings, and as a consequence, the yield of tomatoes, significantly depends on the composition of the substrate used. There is no established understanding among researchers regarding the effectiveness of using one or another material as a substrate, be it peat, perlite, coconut fiber or mineral wool. The difficulty of determining a universal type of substrate that guarantees good germination intensity and the best quality of seedlings prompts the study of the influence of different types of substrate on physiological processes in the tomato plant. The object of the study was the indeterminate tomato hybrid Machitos F1, bred in the Netherlands. The research was carried out in the Kharkov region during 2017-2021. According to the research program, the following types of substrates were studied: mixture – turf soil and humus (65:35) - control; universal nutrient substrate “Generous Earth”; mixture – turf soil and substrate “Jiffy” and humus (1:1:1); peat substrate “Domoflor-mix”. A slight influence of the type of substrate on the timing of the phenological phases of development was noted. The ratio of the mass of the above-ground part of the plant and the root system at the time of planting in the greenhouse when using the substrate “Domoflor-mix” was the highest – 16.5%, however, the seedlings on the substrate “Generous Earth”had the most developed root system. To grow high-quality tomato seedlings, it is recommended to use a mixture – turf soil and substrate “Jiffy” and humus (1:1:1), which allows you to obtain a maximum total yield of 15.7 kg/m2.